Performance analysis of a new solar air ventilator with phase change material: Numerical simulation, techno-economic and environmental analysis. (June 2023) - Barghi Jahromi, Mohammad Saleh; Kalantar, Vali; Samimi Akhijahani, Hadi; Kargarsharifabad, Hadi; Shoeibi, Shahin
Abstract: The solar ventilator for preheating the ambient air has been widely used, due to greenhouse gases emissions and reduces the environmental pollution. In this study, an innovation solar air ventilator with phase change material has been used to increase the air outlet temperature of the system. The solar air ventilator equipped with a copper absorber plate and double-walled glass to reduce heat loss of the system. The sodium carbonate sulfate was used as a phase change material to store the thermal energy of the system and release it when solar radiation is low. The experiments were performed in the climatic condition of Yazd, Iran and compared with numerical results of the system. Transient condition was considered solar ventilator due to varies the ambient air velocity, ambient air temperature and solar radiation parameters during the experiments. The chimney effect was observed in the solar air ventilator due to establishment of an appropriate temperature difference between the body of the solar ventilator and ambient air throughout the day. Results showed that the highest air outlet temperature of the system with and without PCM was reached to 82.6 °C and 74.1 °C, respectively. Moreover, the carbon dioxide mitigation of the system with and without PCM was about 178.2 tons and 80.22 tons, respectively. In addition, cost per cubic meters of air (CPA) of solar ventilator with PCM was 27.3 % more than solar ventilator without PCM. Highlights: An innovation design of solar air ventilator with PCM was evaluated. The flow rate of the air ventilator with PCM was reached 0.031 m 3 /s. Highest air outlet temperature of ventilator with PCM increased by 8.5 °C. The CO2 mitigation of modified air ventilator was enhanced by 2.22 times.